Increased systemic inflammation in children with Down syndrome - Molloy, Eleanor; Roche, Edna; Leahy, Ronan; Doherty, Derek; Franklin, Orla; Balfe, Joanne; Kelly, Lynne (My University, 2020)
Children with Down syndrome (DS) develop more infections, have an increased mortality from sepsis and an increased incidence of chronic inflammatory conditions. Cytokine dysregulation may underpin these clinical sequelae and raised pro-inflammatory biomarkers are a feature in adults with DS. The importance of the anti-inflammatory mediators IL-1ra and IL-10, as well as cytokines Epo and VEGF, which could impact on the pathogenesis and outcomes in congenital heart disease (CHD) which is more prevalent in DS, are less well known. We examined a comprehensive array of pro-(IL-2, IL-6, IL-8, IL-18, IL-1β, TNF-α, IFN-γ), and anti-inflammatory (IL-10 and IL-1ra) mediators, cytokines involved in inflammation in response to hypoxia (EPO), propagating angiogenesis (VEGF), and myelopoiesis (GM-CSF), by enzyme linked immunosorbent assay (ELISA), as well as discussing the potential impact of significant CHD and Lipopolysaccharide endotoxin on these mediators. 114 children with DS and 60 age and sex matched controls were recruited. Children with Down syndrome exhibit significantly greater levels of pro and anti-inflammatory cytokines; IL-2, IL-6, IL-10, IL-1ra, as well as increased Epo, VEGF and GM-CSF at baseline. CHD does not seem to have an impact on circulating cytokines beyond the acute surgical phase. Both cohorts had similar responses to LPS stimulation. These differences may contribute to varied clinical outcomes, acutely like in sepsis, and over time in autoimmunity.
PUBLISHED
Keywords: Cytokines; Down syndrome; Inflammation; Innate immunity; Immunology, Inflammation & Infection; DOWN SYNDROME; INFLAMMATION